Analysis Of The Influence Of Green Accounting, Environmental Performance And Firm Size On Financial Performance - Afika Handayani; Meily Surianti (Jurnal AKSI (Akuntansi dan Sistem Informasi))
This study aims to examine the effect of green accounting, environmental performance, and firm size on financial performance. The background of this study focuses on the growing importance of green accounting practices due to increasing environmental awareness and sustainability among companies, and how these factors can affect a company's financial performance. The data used in this study consists of secondary data in the form of annual reports from non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The sampling method employed was purposive sampling, resulting in 120 data points from 20 companies. The test was conducted using multivariate statistical analysis with the SEM-PLS approach, supported by Smart-PLS software. The findings of this study indicate that green accounting has a negative effect on financial performance, environmental performance has a positive effect on financial performance, and firm size has a negative effect on financial performance. The novelty and main contribution of this study lie in the finding that green accounting does not always have a positive impact on financial performance, which contrasts with previous studies that showed a positive relationship. Additionally, this study provides insights into the impact of environmental performance and firm size on financial performance, offering important considerations for companies when formulating long-term policies and strategies.